Network of urban parks and green corridors in the city of Braga, Portugal - Rocha, Martinha E. R. R. (2012)
The quality of life in urban areas is increasingly becoming a competitive factor for cities. In addition to access to goods and services, access to green spaces and the existence of a sustainable urban environment are key factors to ensure high levels of quality of life in cities. In this context, the present study focuses on the analysis of green spaces integrated in measures promoting urban sustainability. So, it is pertinent that green spaces of a city will be integrated in the city development process, enhancing the respective use. Therefore, it is essential to identify the basis for the creation of connectivity corridors between green spaces, enhancing the interaction between inhabitants and natural landscape, even in urban areas. After a theoretical context of the subject under review, presents the study carried out with the aim of creating an urban green corridors network to the city of Braga, Portugal. One of the major goals is to allow some mitigation of the negative environmental impacts of the city and mobilizing people to leisure, to practice sports, and more sustainable mobility’s, on a daily basis. The study conducted in the city of Braga identifies the viability of creating this urban green corridors network as a way to boost the movement by seeking soft ways and promote an improvement in the quality of the urban environment. Thus, it is concluded that it is possible to adapt the urban space to a new reality, more conscientious at an environmental level.